THE IMPORTANCE OF INTRODUCING POTENTIAL TOURISM DESTINATION THROUGH WRITING ACTIVITY - Sri Endah Kusmartini; Sunani - - (HOLISTICS, 2015)
This is a survey research about the importance of introducing potential tourism destination through writing activity on the basis of the students’ perceptions. The researchers try to find out the importance of introducing potential of tourism destination; to find out the role of writing activity in terms of the potential of tourism destination; and to find out the importance of introducing the potential of tourism destination through writing activity. The population of this research was the students of English Department, State Polytechnic of Sriwijaya, in academic year 2014/2015. The samples which were taken by using purposive sampling were the students of semester three. The results showed that introducing the potential tourism destination especially the ones located in South Sumatera was very important because the province of South Sumatera has a potential tourism destinations which were deserved to be promoted; there was enough effort from the government to introduce the potential tourism destination; It will give revenue for the country; it will create jobs for the community; it will boost economic growth and living standards; and it will stimulate the productivity of other sectors. The roles of writing activity in terms of potential tourism destination were introducing the wealth and the beauty of the nature, the hospitality and the uniqueness of local community, culture, heritage, culinary, and the cultural varieties of the local community to public. Introducing the potential tourism destination through writing activity was very important because there were many international sport events held in South Sumatera. This is a survey research about the importance of introducing potential tourism destination through writing activity on the basis of the students’ perceptions. The researchers try to find out the importance of introducing potential of tourism destination; to find out the role of writing activity in terms of the potential of tourism destination; and to find out the importance of introducing the potential of tourism destination through writing activity. The population of this research was the students of English Department, State Polytechnic of Sriwijaya, in academic year 2014/2015. The samples which were taken by using purposive sampling were the students of semester three. The results showed that introducing the potential tourism destination especially the ones located in South Sumatera was very important because the province of South Sumatera has a potential tourism destinations which were deserved to be promoted; there was enough effort from the government to introduce the potential tourism destination; It will give revenue for the country; it will create jobs for the community; it will boost economic growth and living standards; and it will stimulate the productivity of other sectors. The roles of writing activity in terms of potential tourism destination were introducing the wealth and the beauty of the nature, the hospitality and the uniqueness of local community, culture, heritage, culinary, and the cultural varieties of the local community to public. Introducing the potential tourism destination through writing activity was very important because there were many international sport events held in South Sumatera.